A formação de leitores pelo Projeto Livro do Mês na percepção de discentes e docentes de Escolas Públicas Estaduais de Passo Fundo/RS - D' Arienzo, Maria Augusta (2016)
The work carried out for the formation of readers in three decades of the Jornadas Literárias in the national and state capital of the literature, Passo Fundo, had its ramifications by means of the Projeto Passo Fundo – Capital Nacional da Literatura, including the Projeto Livro do Mês (Book of the Month Project), the corpus of this study. The Projeto Livro do Mês provides students and teachers from different levels of education a monthly contact with the literary work by a contemporary writer, ratifying the methodology of the Jornadas Literárias: the prior reading of the book and later the face meeting with the author. A multimedia reader practice is developed to stimulate discussion of the book among readers. This activity also shows the interaction between the literary work and other readings in different l anguages and different supports aiming to approach these readers in formation of literary texts and form an appreciator audience of different artistic and cultural expressions, in order to consolidate Passo Fundo as National and State Capital of Literature by means of the formation of readers.The central issue of this work is to define to what extent the Projeto Livro do Mês is internalized in school and if it captivates new readers and new ways of reading, and to what extent the proposal of reading developed by the project is incorporated in the reading practices of the students. While the objectives are to investigate if from the participation in the Projeto Livro do Mês there was some change in the relatio nship of students with reading; check if the participation in the project takes students to seek other readings; and establish if from the entrance of the Projeto Livro do Mês at the school there is a transformation in reading practice of teachers with students. Therefore, it seeks on the contributions of Rösing, Chartier, Zilberman, Bahktin, Santaella, Petit, Freire, Iser, Silva, Colomer and Azevedo the understanding of a concept of reading, who is the contemporary reader and how is developed the formation of t he reader in the school context. The analysis was supported by the confrontation between the data described and the theoretical approaches mentioned based on the following categories: the Projeto Livro do Mês in school; the reader before/with the Projeto Livro do Mês; and the reading practices in school. Regarding the methodological procedures, two case studies were conducted gathering the perception of participation in the Projeto Livro do Mês of students and teachers from two schools of the state school system of Passo Fundo. The results of the analysis of the data produced are exposed on three topics that follow the categories mentioned above. The conclusion is that the Projeto Livro do Mês enters the school in two distinct ways: initiative of the teacher and school's desire. It captives new readers and its internalization in the school environment is by means of the involvement of teachers and students in the activities of its different stages and beyond. By the work done previously and after the end of each mont hly edition of the project. Its institutionalization process happens because of the school’s commitment to the formation of readers.